2022
DOI: 10.3390/biomedicines10010092
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Somatostatin-Immunoreactive Cells in the Visual Cortex of the Gerbil

Abstract: Somatostatin (SST) is widely expressed in the brain and plays various, vital roles involved in neuromodulation. The purpose of this study is to characterize the organization of SST neurons in the Mongolian gerbil visual cortex (VC) using immunocytochemistry, quantitative analysis, and confocal microscopy. As a diurnal animal, the Mongolian gerbil provides us with a different perspective to other commonly used nocturnal rodent models. In this study, SST neurons were located in all layers of the VC except in lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…We compared the distributional pattern of NOS-IR neurons in the visual cortex of gerbils with that of other neurochemical markers, i.e., NPY [24] and SST [32]. Notably, we found that the pattern of NOS-IR neurons was similar to that of NPY-IR and SST-IR neurons.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We compared the distributional pattern of NOS-IR neurons in the visual cortex of gerbils with that of other neurochemical markers, i.e., NPY [24] and SST [32]. Notably, we found that the pattern of NOS-IR neurons was similar to that of NPY-IR and SST-IR neurons.…”
Section: Discussionmentioning
confidence: 87%
“…Somatostatin (SST) exhibits widespread expression throughout the brain and plays diverse significant roles [25][26][27][28][29][30][31]. SST-containing neurons are distributed in layers II-VI of the gerbil visual cortex and include four morphologically different cell types [32]. Gamma-aminobutyric acid (GABA) serves as the primary inhibitory neurotransmitter in the CNS and plays a crucial role in the regulation of the balance between excitation and inhibition among neurons [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical research reveals valuable information on human diseases by employing in vitro and in vivo models [ 25 , 26 , 27 , 28 ]. Data collected in-laboratory has made significant contribution to understanding the pathomechanism of human diseases from molecular to organismal levels in search of therapeutic targets [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical research makes a major contribution to prevention, diagnosis, and therapeutic management in clinical medicine, employing in vitro systems and animal models of diseases [ 20 , 21 , 22 , 23 , 24 ]. Experimental research collecting the data from animal studies and animal models of neurodegenerative and neuropsychiatric diseases has provided valuable clues to understanding the roles of endogenous peptides, hormones, and metabolites, searching for useful biomarkers and exploring novel targets for the treatment of diseases [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%